Correction algorithm for combination frame of layer topology of VERY-LarGE-scale INTegration - A. A. Voronov; E. E. Marushko; D. U. Pertsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Correction algorithms for combination frame of layer topology of integrated circuits layout objects and scheme to form a complete image layer without distortion. Results, that was described in this paper, has implementation in computer geometry, image analysis methods.